Peran Kepemimpinan dalam Membangun Budaya Positif di Lingkungan Sekolah - Faras Abiyu; Nasyanda IndahiJoelia; Ermita; Fifin Wildanah (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Leadership iplays ia icrucial irole iin ishaping iand istrengthening ia ipositive ischool iculture, iwhich iis fundamental iin icreating ia iconducive, isafe, iand iinclusive ilearning ienvironment. iSchool iprincipals, ias strategic ileaders, inot ionly imanage iadministrative itasks ibut ialso iserve ias ithe idriving iforce ibehind ithe school’s iculture. iA ipositive ischool iculture iconsists iof ishared ivalues, ibeliefs, inorms, iand ihabits ithat influence ithe ibehavior iof iall ischool imembers. iEffective ileadership, iparticularly itransformational iand instructional istyles, ifosters icollaboration, imotivation, iand iactive iparticipation iamong iteachers, istudents, and iother istakeholders. iThis, iin iturn, ienhances iacademic iachievement iand icharacter idevelopment. However, ichallenges isuch ias iresistance ito ichange, ilimited iresources, iand iinconsistent iimplementation often ihinder ithe iformation iof ia ipositive iculture. iTherefore, iadaptive iand iinclusive ileadership ithat emphasizes iopen icommunication, iinnovation, iand icommunity iinvolvement iis iessential. iPrincipals imust act ias irole imodels iand iinnovators, iintegrating ilocal ivalues iwith iglobal iadvancements ito ibuild ia dynamic iand isustainable ischool iculture. iThis iliterature istudy ihighlights ileadership istrategies ithat effectively ipromote ipositive iculture iin ischools, iemphasizing ithe iimportance iof ilong-term icommitment and icollective iresponsibility.